Consumer Acceptance of Vegetable Protein and No Preservatives in Organic MSG (Monosodium Glutamate) - Prabowo, Kus Alan Dhimas; Tias, Eriza Putri Ayu Ning; Wicaksono, M. Galih; Setyaningsih, Endang (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2024)
Allergy is a response from the body's defense to reject when exposed to certain antigens. When the antigen (allergen) enters the body's tissue, there are two responses produced by the body, namely the allergen that is successful in destroying it or the allergen that damages the body's tissue. Proteins are polypeptide macromolecules composed of a number of L-amino acids linked by peptide bonds. MSG (Monosodium Glutamate) is a gram of sodium derived from glutamic acid. The aim of this research is to determine consumer acceptance of vegetable protein .This research uses quantitative research methods by distributing questionnaires to the public. As well as helping to provide replacement products to people who are allergic to animal protein. The results of the questionnaire that was given to the public, of the 53 respondents who were given the questionnaire, found that 32 respondents chose to use plant-based products and the remainder chose not to use plant-based products. These plants are allergic to animal protein and the rest do not experience allergies.